Factors affecting the business success of small and medium food enterprises in the Philippines - Borazon, Elaine Quintana; Supangco, Vivien Dr. (Quezon City Cesar E. A. Virata School of Business, University of the Philippines Diliman, 2014)
Determines the factors that influence the business success of small and medium food enterprises in the Philippines. A survey of 233 food enterprises was conducted and structural equation modeling was used to test the hypotheses. Recommends also that cross-cultural research can also be done to develop a generalizable model for factors affecting the business success of small and medium enterprises.
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Food industry and trade -- Philippines; Small business -- Philippines; Strategic planning